Research-based teaching and learning (RBTL) - a paradigm for enhancing teaching and learning at research universities - Anja Pawelleck; Sabine Brendel (Universitat Politècnica de València, 2013)
Although universities are established seats of research and teaching (teaching-research-nexus), the two fields often remain separate, with students cut off from current research. Yet, to develop a critical approach to academic issues and research, it is essential for students to be exposed to current research. The text explores an "research based teaching and learning" (RBTL) training model currently being developed by the University of Zurich, a leading research-oriented university, wich is designed to draw on the research skills and experience of its academic staff in encoutaging them to integrate current research into their teaching. In this learner-centered model, the aim is for university students to learn about the research process and develop their own research skills. Recent research will be briefly reviewed.